Manifestation of Benevolence and Humanitarianism in Vietnamese Penal Codes and Solutions for Improvement in the New Era - Chi, Nguyễn (VNU Journal of Science: Legal Studies, 2026)
Based on a historical-comparative approach, this article analyzes the consistent and increasingly profound expression of humanitarian and rehabilitative values in the Vietnamese Penal Codes, and clarifies the shift in legislative thinking from a focus on punishment to an emphasis on prevention, education, and restoration. On the basis of this research, the author finds that it is necessary to continue improving Vietnamese criminal law in the direction of enhancing its humanitarian and rehabilitative orientation in the current period. The article proposes several solutions, including reviewing and eliminating criminal provisions that improperly criminalize civil and economic relations; reducing and limiting the application of the death penalty; strengthening the use of non-custodial penalties; and studying the application of restorative justice philosophy, with greater emphasis on mediation and civil compensation instead of criminal prosecution. Keywords:  .